2015
DOI: 10.1590/1807-3107bor-2015.vol29.0019
|View full text |Cite
|
Sign up to set email alerts
|

CBCT-based evaluation of integrity of cortical sinus close to periapical lesions

Abstract: The purpose of the present study was to test the applicability of cone beam computed tomography (CBCT) to evaluate the integrity of the cortical sinus close to periapical lesions. Two observers analyzed samples of 64 alveoli of first molar roots in macerated swine maxillas prepared with perchloric acid to simulate periapical lesions. The specimens were evaluated using CBCT (55-mm high and 100-mm diameter cylinder at 0.2-mm voxel resolution) for the presence of oroantral communication (OAC) caused by the simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Currently, CBCT serves as the standard diagnostic method for dental pathologies. Dental CBCT affords a high spatial resolution and accurate detection of periapical lesions, oroantral fistulae, and periodontal diseases, especially in upper maxillary teeth [ 15 , 29 , 30 ]. We found that CPR had an acceptable sensitivity in detecting pathologies in the molars, which are the teeth most commonly involved in odontogenic sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, CBCT serves as the standard diagnostic method for dental pathologies. Dental CBCT affords a high spatial resolution and accurate detection of periapical lesions, oroantral fistulae, and periodontal diseases, especially in upper maxillary teeth [ 15 , 29 , 30 ]. We found that CPR had an acceptable sensitivity in detecting pathologies in the molars, which are the teeth most commonly involved in odontogenic sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the choice of the CBCT image for distance analysis might have influenced the measurements, since only one observer had assessed the radiographs. Furthermore, an experimental study has shown some difficulty for evaluation of the integrity of the cortical sinus floor close to a periapical radiolucency (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, although it revealed unilateral sinusitis, it did not detect the OAC. The difficulty in observing the discontinuity of the bony floor of the maxillary sinus may have been due to a high level of image noise [ 15 ].…”
Section: Discussionmentioning
confidence: 99%